2015
DOI: 10.28930/jitkt.v6i2.9015
|View full text |Cite
|
Sign up to set email alerts
|

NATURAL FEED (ROTIFER) MANAGEMENT ON ORANGE SPOTTED GROUPER Epinephelus coioides LARVAL REARING

Abstract: According to Indonesian Standard Quality, the optimal seed production of orange spotted grouper (Epinephelus coioides) Keywords: rotifers, feeding time, Orange Spotted grouper larvae, Epinephelus coioides ABSTRAKProduksi benih ikan kerapu lumpur (Epinephelus coioides) dalam jumlah yang optimal dan kualitas yang sesuai Standar Nasional Indonesia (SNI) masih belum dapat dipenuhi, seiring dengan terjadinya berbagai kendala selama periode pemeliharaan larva. Upaya pemeliharaan larva secara masal telah dilakukan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…and Oithona sp.) (Toledo et al, 1999) to 8.8 ± 2.26% when using different combinations of feed and tank size (Aslianti & Setyadi, 2014) and finally to 9.3 ± 4.9% when fed with rotifers and pond collected copepods (Yousif et al, 2016). Fourooghifard et al (2017) had reported maximum larval survival of 16 ± 9.94% after 30 days of rearing; however, at metamorphosis on 43 DPH, survival rate was not estimated and, therefore, results appear inconclusive.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…and Oithona sp.) (Toledo et al, 1999) to 8.8 ± 2.26% when using different combinations of feed and tank size (Aslianti & Setyadi, 2014) and finally to 9.3 ± 4.9% when fed with rotifers and pond collected copepods (Yousif et al, 2016). Fourooghifard et al (2017) had reported maximum larval survival of 16 ± 9.94% after 30 days of rearing; however, at metamorphosis on 43 DPH, survival rate was not estimated and, therefore, results appear inconclusive.…”
Section: Resultsmentioning
confidence: 99%
“…Optimizing the feeding protocol during various phases of larval rearing culminated in a larval survival rate, which is the highest ever recorded for the species. Earlier workers (Aslianti & Setyadi, 2014; Doi et al, 1991; Duray et al, 1997; Lim, 1993; Su et al, 1997; Toledo et al, 1999; Yousif et al, 2016), during larval rearing for orange‐spotted grouper, had not attempted to optimise the densities and combinations of live feed, and their supplementation during larval rearing was more depending on the availability rather than on the requirement. Therefore, optimum larval survival for orange‐spotted grouper has never been achieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Environment is the most important factor for grouper cultivation in ponds or KJA (Rumondang et al, 2020); (Annur et al, 2021). The growth of grouper is relatively rapid; consequently, both the local market and the export market can be satisfied (Aslianti and Setyadi, 2015).…”
Section: Introductionmentioning
confidence: 99%